Radiocephalic Fistula Recovery Using the Brachial Vein and Forearm Basilic Vein: A Case Series and Literature Review. Issue 6 (25th July 2018) - Norton de Matos, António; Sousa, Clemente N; Almeida, Paulo; Teles, Paulo; Rego, Duarte; Teixeira, Gabriela; Loureiro, Luís; Teixeira, Sérgio; Antunes, Inês
Abstract: Vascular access dysfunction is a serious problem in dialysis units. Some patients have complex dysfunctions that are difficult to resolve. In this article, we report the case a of two patients with radiocephalic arteriovenous fistulae (RC‐AVF) who had stenosis/occlusion of the forearm median vein and where we used the basilic vein of the forearm as a solution. We reviewed the use of this surgical solution in RC‐AVF. Two male patients on hemodialysis exhibited stenosis/occlusion of the forearm median vein. The forearm basilic vein was isolated and rotated toward the forearm median vein in order to solve RC‐AVF problems. One patient had fistula thrombosis 5 months after the procedure, while for the other patient, the fistula continues to work without problems. Literature describes only a few cases using the forearm basilic vein or the brachial vein for fistula recovery. This procedure increased the patency of fistulas. This approach has been proven to be a good solution for solving outflow problems using the superficial or deep veins, increasing fistula patency and avoiding the need to place a central venous catheter and all the related complications.